Therapists’ experiences of remote working during the COVID-19 pandemic - Morgan, Andrew; Davies, Cari; Olabi, Yasmine; Hope-Stone, Laura; Cherry, Mary Gemma; Fisher, Peter (Frontiers in Psychology, 2022)
Objectives: To explore the experiences of therapists who delivered remote psychological therapy during the COVID-19 pandemic. Design: This was a qualitative, phenomenological study. Interpretative Phenomenological Analysis elicited themes from semi-structured interviews. Methods: A purposive sample of 8 therapists was recruited from breast cancer services in the United Kingdom. Results: Analysis identified 3 superordinate themes. Participants spoke about how their experience of remote working changed over time from an initial crisis response to a new status quo. They adapted to the specific practical and personal challenges of remote working and struggled to connect with clients as the use of technology fundamentally changed the experience of therapy. Conclusion: Consideration should be given to the impact of remote working on therapists and the quality of their practice. Adjustments to ways of working can help to maximise the advantages of remote working whilst minimising potential issues.